2006
DOI: 10.1111/j.1440-1819.2006.01532.x
|View full text |Cite
|
Sign up to set email alerts
|

Total antioxidant response in patients with schizophrenia

Abstract: There is a large amount of convincing data demonstrating that reactive oxygen species (ROS) are involved in initiation and development of many different forms of neuropsychiatric disorders. The levels of oxidants and antioxidants in schizophrenia have been evaluated. However, measurements of total antioxidant response (TAR) were not evaluated up to now. Therefore, the objectives of this study are to investigate plasma TAR levels in schizophrenia subtypes. A total of 76 patients with schizophrenia and 25 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
26
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 33 publications
5
26
2
Order By: Relevance
“…Determination of total antioxidant capacity serves as an indicator for all antioxidants [24,49]. In line with our study, lower plasma TAL values were reported in patients with schizophrenia in the studies conducted using the same method [24,50,51]. In other words, it may be expressed that antioxidant defense mechanisms against oxidative stress may differ according to the individuals and environmental conditions.…”
Section: Discussionsupporting
confidence: 83%
“…Determination of total antioxidant capacity serves as an indicator for all antioxidants [24,49]. In line with our study, lower plasma TAL values were reported in patients with schizophrenia in the studies conducted using the same method [24,50,51]. In other words, it may be expressed that antioxidant defense mechanisms against oxidative stress may differ according to the individuals and environmental conditions.…”
Section: Discussionsupporting
confidence: 83%
“…The total antioxidant plasma capacity is not a simple sum of the various antioxidant substances, but includes a dynamic equilibrium that is influenced by the interactions between different serum antioxidant constituents. The present study demonstrated a significant reduction in plasma TAS of patients with schizophrenia compared to healthy controls, this finding was in agreement with similar study conducted by Ustundag et al 44 The brain is preferentially susceptible to oxidative damage since it is under very high oxygen tension and highly enriched in reactive oxygen species (free radicals), susceptible proteins, lipids and poor DNA repair. 45 …”
Section: Discussionsupporting
confidence: 94%
“…Therefore, studies examining antioxidant parameters in patients with schizophrenia are confl icting. Some studies have shown increased antioxidant levels in patients with schizophrenia (23)(24)(25)(26), while some have shown a decrease (22,27,28), and still some have found no change (29)(30)(31). Our results showed an increase in oxidant levels and no change in antioxidants in patients with schizophrenia.…”
Section: Discussionsupporting
confidence: 33%